Trump Indictments : the historic charging documents with commentary - Murray, Melissa; Weissmann, Andrew (New York , NY W. W. Norton & Company, 2024)
"Timed to the start of the first trial in March 2024, this essential volume collects the four unprecedented indictments against Donald Trump and features extensive commentary by NYU law professors and MSNBC contributors Melissa Murray and Andrew Weissmann. In the long span of American history, Donald Trump is the first former president to face criminal indictment. He is the subject of a series of explosive charges across four cases: the January 6 case brought by Special Counsel Jack Smith; the election interference case in Georgia; the classified documents case also brought by Special Counsel Jack Smith; and the "hush money" case in New York."--
Preface: the purpose of this book -- Introduction -- Chronology of key dates -- United States of America v. Donald J Trump (DC January 6 indictment) -- The state of Georgia v Donald John Trump, et al (Fulton County, Georgia indictment) -- United States of America v. Donald J. Trump et al (Southern district of Florida indictment) -- The people of the state of New York v. Donald J Trump (New York indictment) -- Complete cast of characters.
113333
Keywords: Trump, Donald -- 1946- -- Trials, litigation, etc; United States -- Department of Justice; Indictments -- United States; Security classification (Government documents); Elections -- Corrupt practices -- United States; Political campaigns -- Corrupt practices -- United States; Political corruption -- United States; Informational works